Rapid Analysis Procedures for Triglycerides and Fatty Acids as Pentyl and Phenethyl Esters for the Detection of Butter Adulteration Using Chromatographic Techniques - Daniele Naviglio; Marina Dellagreca; Francesco Ruffo; Anna Andolfi; Monica Gallo (Journal of Food Quality)
This paper presents the development of three methods for quality control, fraud detection, and authentication of butter fat and other oils/fats using chromatographic techniques, with one method for triglycerides and two methods for fatty acids (FAs). The procedure for the analysis of triglycerides requires only dissolution of the sample in n-hexane and gas chromatography (GC) analysis using a capillary column. The second method is based on the transesterification of triglycerides as pentyl esters in a single-step reaction using sodium pentanoate in pentanol. The reaction proceeds at room temperature and is similar to the potassium hydroxide-catalysed transesterification of triglycerides with methanol and even more similar to the sodium methoxide method and sodium butanoate method. The advantage of using pentyl esters includes reducing the volatility of short-chain FAs, and substantial recoveries were obtained compared with methyl ester analysis. The third method involves the transesterification of triglycerides in fat through reaction with 2-phenylethanol in a single step; 2-phenylethanol possesses a chromophore, and the phenethyl esters formed are analysed by high-performance liquid chromatography (HPLC) with UV detection.